Factors affecting the decline in statistics department enrollment: A comparative study of statistics department students and twelfth-grade students - Hazhar Talaat Abubaker Blbas; Asma Muhamad Kakil; Zahra Abdulstar Ahmad; Sara Fuad Ahmad (Social Sciences and Humanities Open)
The purpose of this study is to investigate the factors influencing students' hesitancy to enroll in the Statistics Department at Salahaddin University. Both anecdotal evidence and actual enrollment data indicate a decline in enrollment within this department. Despite considerable speculation regarding the potential causes of this reduction, there is a notable absence of targeted studies addressing the issue. Data for this study were collected through a questionnaire administered from October 16, 2022, to January 19, 2023, to students in both the Statistics Department and twelfth-grade students in Erbil, Iraq. The questionnaire consisted of two sections: demographic questions and inquiries regarding the factors that deter students from pursuing studies in the Statistics Department. Using statistical techniques for data analysis, including factor analysis and classification methods, this study identifies key challenges contributing to the decline in enrollment. Foremost among these is the mismatch between graduate employability and labor market demands, with both private and public sector entities reluctant to hire graduates due to limited industry collaboration. Additionally, curriculum design and pedagogical challenges in statistics reveal an over-reliance on theoretical content at the expense of practical applications, alongside language barriers that hinder global employability. Furthermore, determinants of educational choices such as limited awareness of the department and restrictive admission policies further complicate student recruitment efforts. These findings underscore the urgent need for higher education institutions to implement curricular reforms, strengthen industry partnerships, and enhance communication strategies to better align the department's offerings with market demands and student expectations.